Isolation and characterization of novel Dothideomycetes species from forest soils in Chiang Rai and Krabi (Thailand): additions to the diversity of Curvularia and Verruconis - Yasanthika, W. A. Erandi; Tennakoon, Danushka S.; Farias, Antonio R. Gomes De; Chethana, K. W. Thilini; Bhat, D. Jayarama; Wanasinghe, Dhanushka N. (Phytotaxa, 2023)
Fungi are adapted to diverse environments, where the forest soils have complex fungal communities with a wide range of lifestyles. This study aims to explore and isolate Dothideomycetes from the forest soils in Thailand. Sampling sites were located in Chiang Rai and Krabi provinces. Cultures were obtained through soil dilution series, and the strains were subjected to morphological observations and multigene phylogenetic analyses for identification. Maximum likelihood and Bayesian inference analyses were conducted to clarify their phylogenetic affinities using partial nuclear ribosomal DNA (ITS, LSU, and SSU) and the protein-coding genes (tef1-α and GADPH). Herein, two new species (Curvularia chiangraiensis sp. nov. and Verruconis soli sp. nov.) and two new records (C. chiangmaiensis and V. thailandica) are described based on the morphological and phylogenetic evidence. Curvularia chiangraiensis sp. nov. is distinguished by its relatively smaller conidia and the presence of sympodial proliferation of conidiogenesis and Verruconis soli sp. nov. exhibits micronematous conidiophores and obovoid conidia that transform into sub-cylindrical or ellipsoidal shapes, and becoming 1-septate when mature. These unique characteristics set them apart from closely related taxa. The newly described taxa have been subjected to a thorough comparison with closely related species, enabling a comprehensive analysis. The study offers detailed descriptions and includes high-quality micrographs, with the aim of providing a comprehensive understanding of these newly identified taxa